2017
DOI: 10.1128/mcb.00668-16
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 Plays an Important Role in Skeletal Development by Controlling Preosteoblast Differentiation

Abstract: The mammalian target of rapamycin complex 1 (mTORC1) is activated by extracellular factors that control bone accrual. However, the direct role of this complex in osteoblast biology remains to be determined. To investigate this question, we disrupted mTORC1 function in preosteoblasts by targeted deletion of Raptor (Rptor) in Osterix-expressing cells. Deletion of Rptor resulted in reduced limb length that was associated with smaller epiphyseal growth plates in the postnatal skeleton. Rptor deletion caused a mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(89 citation statements)
references
References 76 publications
(96 reference statements)
6
80
0
3
Order By: Relevance
“…Mice in which Raptor , an essential component of mTORC1, is deleted in OBs ( Rptor OB −/− ) are severely osteopenic and Raptor null OBs fail to undergo mineralization (Chen & Long, ; Fitter et al, ); bone phenotypes that are similar to InsR OB−/− and Gprc6a −/− mice (Fulzele et al, ; Pi et al, ). Transcriptomic analyses revealed that raptor null OBs have an immature bone phenotype, suggesting that mTORC1 signaling is crucial for the differentiation of pre‐OBs into mature OBs (Chen & Long, ; Fitter et al, ). Importantly, total OCN levels are significantly decreased in Rptor OB −/− mice (Fitter et al, ).…”
Section: Skeletal Insulin Resistance Disrupts Whole‐body Glucose Homementioning
confidence: 99%
See 2 more Smart Citations
“…Mice in which Raptor , an essential component of mTORC1, is deleted in OBs ( Rptor OB −/− ) are severely osteopenic and Raptor null OBs fail to undergo mineralization (Chen & Long, ; Fitter et al, ); bone phenotypes that are similar to InsR OB−/− and Gprc6a −/− mice (Fulzele et al, ; Pi et al, ). Transcriptomic analyses revealed that raptor null OBs have an immature bone phenotype, suggesting that mTORC1 signaling is crucial for the differentiation of pre‐OBs into mature OBs (Chen & Long, ; Fitter et al, ). Importantly, total OCN levels are significantly decreased in Rptor OB −/− mice (Fitter et al, ).…”
Section: Skeletal Insulin Resistance Disrupts Whole‐body Glucose Homementioning
confidence: 99%
“…Transcriptomic analyses revealed that raptor null OBs have an immature bone phenotype, suggesting that mTORC1 signaling is crucial for the differentiation of pre‐OBs into mature OBs (Chen & Long, ; Fitter et al, ). Importantly, total OCN levels are significantly decreased in Rptor OB −/− mice (Fitter et al, ). While this may be secondary to the stall in osteogenesis, these data provide evidence that mTORC1 in OBs is important for OCN expression.…”
Section: Skeletal Insulin Resistance Disrupts Whole‐body Glucose Homementioning
confidence: 99%
See 1 more Smart Citation
“…As a vital regulator of cell metabolism and proliferation, mTORC1 is ubiquitously expressed in all mammalian cell types [20]. A key role of mTORC1 in bone formation was originally identified in almost all skeleton-related cell lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Primary stromal cells were isolated and cultured from 4-week-old EfnB1 fl/fl mice as described previously [32]. Cells from EfnB1 fl/fl mice were infected with a lentivirus containing the tamoxifen-inducible self-deleting Cre recombinase LEGO-CreERT2-iG2) in the presence of Polybrene (4 mg/mL) as described previously [61,62]. Stably transduced cells were selected by FACS based on enhanced green fluorescent protein expression.…”
Section: Letriviral Transductionmentioning
confidence: 99%